Optical and electronic signal stabilization of plasmonic fiber optic gate electrodes: towards improved real-time dual-mode biosensing - Hasler, Roger; Steger-Polt, Marie-Helene; Reiner-Rozman, Ciril; Fossati, Stefan; Lee, Seungho; Aspermair, Patrik; Kleber, Christoph; Ibáñez, Maria; Dostalek, Jakub; Knoll, Wolfgang (Frontiers in Physics, 2023)
The use of multimodal readout mechanisms next to label-free real-time monitoring of biomolecular interactions can provide valuable insight into surface-based reaction mechanisms. To this end, the combination of an electrolyte-gated field-effect transistor (EG-FET) with a fiber optic-coupled surface plasmon resonance (FO-SPR) probe serving as gate electrode has been investigated to deconvolute surface mass and charge density variations associated to surface reactions. However, applying an electrochemical potential on such gold-coated FO-SPR gate electrodes can induce gradual morphological changes of the thin gold film, leading to an irreversible blue-shift of the SPR wavelength and a substantial signal drift. We show that mild annealing leads to optical and electronic signal stabilization (20-fold lower signal drift than as-sputtered fiber optic gates) and improved overall analytical performance characteristics. The thermal treatment prevents morphological changes of the thin gold-film occurring during operation, hence providing reliable and stable data immediately upon gate voltage application. Thus, the readout output of both transducing principles, the optical FO-SPR and electronic EG-FET, stays constant throughout the whole sensing time-window and the long-term effect of thermal treatment is also improved, providing stable signals even after one year of storage. Annealing should therefore be considered a necessary modification for applying fiber optic gate electrodes in real-time multimodal investigations of surface reactions at the solid-liquid interface.